The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1159/000368160
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Cholestyramine on Postprandial Secretions of Cholecystokinin and Peptide YY in Women with Bulimia Nervosa

Abstract: Objective: Patients with bulimia nervosa (BN) are reported to have decreased postprandial levels of cholecystokinin (CCK) and peptide YY (PYY). Fatty nutrients are the most powerful stimulus for releasing these peptides. Cholestyramine is an anion exchanger which adsorbs bile salts and reduces the digestion of lipids, affecting the secretion of both CCK and PYY. To further characterise the physiology of these peptides in BN, we aimed to investigate the effects of cholestyramine (12 g, per os) or placebo admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…PYY predicted increased fullness, gastrointestinal distress, and urge to vomit. Prior studies of BN and BNp employing a similar test meal have found either lower (Kojima et al, ; Monteleone et al, ; Rigamonti et al, ) or no significant alteration in postprandial PYY response compared to healthy controls (Devlin et al, ), suggesting that exaggerated PYY response distinguishes PD from BNp. This is the first study to identify a specific biological dysregulation in PD.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…PYY predicted increased fullness, gastrointestinal distress, and urge to vomit. Prior studies of BN and BNp employing a similar test meal have found either lower (Kojima et al, ; Monteleone et al, ; Rigamonti et al, ) or no significant alteration in postprandial PYY response compared to healthy controls (Devlin et al, ), suggesting that exaggerated PYY response distinguishes PD from BNp. This is the first study to identify a specific biological dysregulation in PD.…”
Section: Discussionmentioning
confidence: 95%
“…The best-fitting model for ghrelin (BIC 5 4705.69) showed a signif- Figure 1b). (Kojima et al, 2005;Monteleone et al, 2005;Rigamonti et al, 2014) or no significant alteration in postprandial PYY response compared to healthy controls (Devlin et al, 2012), suggesting that exaggerated PYY response distinguishes PD from BNp. This is the first study to identify a specific biological dysregulation in PD.…”
Section: Gut Peptide Responsesmentioning
confidence: 91%
“…In particular, in the present study, we evaluated the circulating levels of gut peptides in a single time-point. As demonstrated in medical literature [61][62][63], the altered secretion in eating disorders should be investigated dynamically with more time-points. Nevertheless, as specified in our protocol, the sampling conditions were strictly standardized: The patient's blood sample was drawn at 08.00-11.00 a.m. after an overnight fast.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found a blunted increase in PYY levels after test meals in patients with BN [78][79][80], while no difference in PYY levels were observed in female patients with BED [81]. Furthermore, there was a negative correlation between postprandial PYY levels and binge frequency in women [80], although it is again unclear if altered PYY levels contribute to the development of disordered eating behaviors or are a consequence of it. While several clinical trials are investigating the use of intranasal PYY in the treatment of obesity, no trials are currently registered to examine PYY agonists in the treatment of EDs.…”
Section: Binge Eating In Bn and Bed Neuroendocrinementioning
confidence: 99%